Reversing the School to Prison Pipeline: The Impact of an Adult High School Program - Emily Merola; David C. Phillips; Patrick S Turner (Institute of Labor Economics (IZA), 2025)
The criminal justice system primarily arrests and incarcerates people without high school diplomas. We estimate the causal effect of a high school diploma on criminal justice system contact for a set of people who previously exited high school but then attended The Excel Center (TEC), a network of high schools for adults. Compared to those who apply but do not enroll, students who enroll but exit without a diploma do not experience a decline in criminal charges. Criminal charges for students who complete a diploma, on the other hand, decline by 49% the year following application, an effect which largely persists for at least five years. These effects are sufficiently large to increase the cost-effectiveness of the program by 2-5 times. The pattern of effects also suggests that, beyond simple incapacitation, getting an adult high school diploma itself leads to lower contact with the criminal justice system.
Keywords: K42; I24; I26; 330; high school diploma; returns to education; human capital; GED; crime